DESCRIPTIVE ANALYSIS ABOUT ARABICIZING OF FOREIGN NOMENCLATURES INTO ARABIC AND ITS IMPLICATIONS TO TARJAMAH LESSON - Zenno Noeralamsyah, - (2008)
This is a descriptive analysis research which was aimed to find out the arabicized words consist in Arabic lexicography, book and magazine writing. It is a literal research that search for Arabization procedure occurred in Arabic inscription of foreign nomenclatures (English and Indonesian). Ta'rīb (Arabization, Arabicizing) is a language phenomenon caused by social interaction between Arabic and the others. It is made a renewal demand of modern lexicography and dictionary. A new terminology of contemporary sciences and cultural fields there will always appear throughout the time. In context of Arabic language, ta'rīb means Arabicizing of foreign terminologies, and its letter unit into Arabic. The development of sciences and knowledges made an appearences of new terninologies and nomenclatures that never found before in classical dictionaries like Lisān al-Arab (written by Ibn a-Manzh$3;r). This kind of phenomenon need to solve, because the Arabic and the non-Arabic speaker need to understand the words, with no caused damaged to Arabic grammatical system and be biased in semantic side. One of the differences is the inexistence of some phonetic symbols in Arabic, which exists in English and Indonesian. Such as "ص", "ض", "ظ", "ذ", which are not found in other language. This also happen to several writers and translators, occasionally they apply an Arabicing differently each other. Sometimes, "جـ", "غ","ق" , or "ك" applied to substitute "g" in English and Indonesian. The data were collected by gathering the arabicized terminologies obtained at modern Arabic-English and English-Arabic dictionary, Arabic magazines, and journal. Such as the 3760 words found as arabicized terminologies in "Al-Mawrid" (English-Arabic) dictionary.